Investigation of spatial variations in collection efficiency of solar cells - Hiltner, Jason F., author; Sites, James R., advisor; Gelfand, Martin P., committee member; Menoni, Carmen, committee member; Field, Stuart, committee member (Colorado State University. Libraries, 2001)
In an effort to investigate spatial variations in solar cells, an apparatus which is capable of mapping collection efficiency with micron resolution and near-solar intensity has been developed. Local reductions in collection are observed in CdTe- and Cu(In1–xGax)Se2-based devices, and are characterized by measuring the response as a function of cell bias and incident laser intensity. By modeling this data with an equivalent circuit, it is clear that the majority of local variations in the response are due to series resistance variations. Further, direct evidence is given for bandgap variations in CdTe solar cells, which are correlated with high resistance regions in some devices. The bandgap variation is attributed to diffusion of S into CdTe, forming the lower bandgap CdTe1–xSx, during the post-deposition CdCl2 treatment commonly used to improve performance. Investigation of the impact of CdCl2 on a CdTe solar cell indicates that the treatment reduces the number of variations seen with above-bandgap photon energies, but also increases local variations in bandgap. The latter effect has been attributed to non-uniform penetration of CdCl2 to the device interface. Finally, elevated-temperature stress on CdTe devices is shown to preferentially degrade regions which exhibit decreases in bandgap, and hence increased S alloying.
Keywords: condensation; optics; condensed matter physics